Outcomes of Revision Arthroscopic Posterior Labral Repair and Capsulorrhaphy: A Systematic Review. Issue 5 (23rd May 2023) - Jewett, Callie A.; Reardon, Patrick; Cox, Charles; Bowman, Eric; Wright, Rick W.; Dickens, Jonathan; LeClere, Lance
Background: Failure rates up to 14% have been reported after arthroscopic posterior capsulolabral repair. It is unknown if revision arthroscopic posterior capsulolabral stabilization has inferior restoration of stability and return to sport when compared with primary repair. Optimal management of failed posterior capsulolabral stabilization is unknown. Purpose: To report outcomes of revision posterior capsulolabral repair and factors that contribute to failure and to determine optimal management of failed posterior stabilization procedures. Study Design: Systematic review; Level of evidence, 4. Methods: A computerized search of the PubMed, EMBASE, and Web of Science databases and manual screening of selected article reference lists were performed in January 2022. Randomized controlled trial, cohort, case-control, and case series studies reporting clinical outcomes of revision arthroscopic posterior capsulolabral repair were eligible. Patient characteristics, indications for revision, intraoperative findings, surgical techniques, and patient-reported outcomes were recorded. Owing to heterogeneity of reported outcomes, data were summarized and presented without pooled statistics. Results: Only 3 of the 990 identified studies met inclusion criteria. The included studies encompassed 26 revision arthroscopic posterior capsulolabral repairs, with follow-up ranging from 2.3 to 5.3 years. The failed index procedure was arthroscopic capsulolabral repair with suture anchors (n = 22) or posterior thermal capsulorrhaphy (n = 4). The primary indications for revision were recurrent instability and pain. Six patients experienced recurrent instability after revision. Patient satisfaction ranged from 15% to 25%. Conclusion: This systematic review of 3 studies demonstrated that the incidence of persistent pain and recurrent instability after revision arthroscopic posterior shoulder stabilization is common, and despite slight improvement in patient-reported outcomes, many patients are dissatisfied with their clinical outcomes. Revision arthroscopic posterior shoulder stabilization appears to have a significant failure rate, and there is need for additional prospective studies to help determine the best intervention for these patients.